2012
DOI: 10.1038/cdd.2012.59
|View full text |Cite
|
Sign up to set email alerts
|

cIAP1 and cIAP2 limit macrophage necroptosis by inhibiting Rip1 and Rip3 activation

Abstract: Cellular inhibitor of apoptosis proteins (cIAPs) have emerged as important anti-cell death mediators, particularly in cancer. Although they are known to be expressed in immune tissue, their specific immune function remains unclear. We observed that degradation of cIAPs with SMAC mimetic (SM) results in death of primary bone-marrow-derived macrophages. SM-induced death of macrophages occurred by programmed necrosis (necroptosis), which was dependent on TNF receptor expression. Consistent with necroptosis, SM-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 45 publications
4
92
2
Order By: Relevance
“…Treatment with a mimetic of the second mitochondrial activator of apoptosis (SMAC) induces regulated cell death of macrophages even in the absence of any PAMP stimulation, and this is induced by rapid degradation of cIAPs by SMAC. 29 Stimulation of macrophages with the SMAC mimetic, birinapant (BP) resulted in a significant loss of cell viability, which was further enhanced by co-treatment with zVAD, and was rescued by treatment with Nec-1 ( Figure 4a). Interestingly, RIPK1…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with a mimetic of the second mitochondrial activator of apoptosis (SMAC) induces regulated cell death of macrophages even in the absence of any PAMP stimulation, and this is induced by rapid degradation of cIAPs by SMAC. 29 Stimulation of macrophages with the SMAC mimetic, birinapant (BP) resulted in a significant loss of cell viability, which was further enhanced by co-treatment with zVAD, and was rescued by treatment with Nec-1 ( Figure 4a). Interestingly, RIPK1…”
Section: Resultsmentioning
confidence: 99%
“…CYLD is required for necroptosis induction by deubiquitinating RIP1, whereas the involvements of other deubiquitinating enzymes that trigger RIP1 deubiquitination such as A20, USP21 and cezanne in necroptosis induction are currently unknown (46)(47)(48)86). Inhibition of cIAP function, which is critical for RIP1 polyubiquitination, by genetic deletion or pharmacological methods, has been reported to sensitize cells to necroptotic cell death by preventing RIP1 K63-linked ubiquitination (49,78,(87)(88)(89)(90). RIP1 deubiquitination leads to the formation of complex II, which is composed of TRADD, FADD, RIP1 and caspase-8 (91).…”
Section: Mechanism Of Tnf-induced Necroptosismentioning
confidence: 99%
“…On one hand, necroptotic cell death has been shown to aid in activating an immune response to some viruses (8,9). On the other hand, we have previously shown that increased necrotic cell death in cellular inhibitor of apoptosisdeficient macrophages results in impaired control of bacteria (10). In addition, necroptotic cell death has been shown to perpetuate various inflammatory pathologies (4,11).…”
mentioning
confidence: 99%